STRATEGI INDONESIA DALAM MENANGGAPI RESOLUSI PARLEMEN UNI EROPA NO. P8_TA(2017)0098 TENTANG PALM OIL AND DEFORESTATION OF RAINFOREST TAHUN 2017 - Maya Bonita; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Parliament of the European Union issued a resolution on palm oil in April 2017.The resolution is titled Palm Oil and Deforestation of Rainforest. The resolution isconsidered discriminatory against palm oil because it recommends other vegetable oils thatare no more efficient than palm oil. The discrimination of palm oil has been going on for along time, but this time the Uni European-levelissued the resolution. This is contrary to theprinciples established by the Eurepoean Union so far as the champion of open, rules-basedfree, and fair trade.This research uses Library Research method. The data is obtained from the officialwebsite of the relevant institutions both from Indonesia and the Parliament of the EuropeanUnion. Using the perspective of Mercantilism, the level of Country-Nation analysis andCompetitive Advantage Theory proposed by Michael E. porter and the Concept of NationalInterest.Indonesia as the world's largest palm oil producer feels very disappointed with theissuance of the resolution. Moreover, Indonesia has strived to create the Palm Oil Industrythat is compatible with sustainable development. Indonesia needs a special strategy so thatthe resolution is not implemented because it will have a political impact and a bad image onthe European Union countries and other countries due to restrictions on palm oil. However,Indonesia is not alone. Indonesia along with other palm oil producing countries unite to fightthe resolution and show the facts through a positive campaign that palm oil is a moreefficient, effective and sustainable type of vegetable oil. Finally, the use of palm oil iscontinued and there is no discrimination and the European Union will onlyincrease the use of renewable energy to 32% by 2030.Keywords : Palm Oil, Vegetable Oil, European Parliament, Mercantilism Perspective,Resolution